1987
DOI: 10.1007/bf02714452
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of gallium scan, angiotensin-converting enzyme level, and bronchoalveolar lavage in two-year follow-up of pulmonary sarcoidosis

Abstract: Evaluation of patients with pulmonary sarcoidosis with serum angiotensin-converting enzyme (ACE), gallium scan, and bronchoalveolar lavage (BAL) has proved useful in demonstrating active disease, especially in the lungs. Long-term prognosis based on the results of pretreatment ACE, gallium scan, and BAL has not been previously clarified. We studied 44 patients with initially symptomatic pulmonary sarcoidosis who were begun on steroid therapy after initial evaluation. At 2 years, 21 of 44 (48%) patients still h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
3

Year Published

1988
1988
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 18 publications
2
17
0
3
Order By: Relevance
“…In agreement with other authors (Bourguet et al 1986;Alberts and Van der Schoot 1988;Baughman and Eisentrout 1986), our experience suggests that the absolute quantitation of 67Ga lung uptake appears to be a suitable marker of disease activity in sarcoidosis. It is useful for the delineation of residual X-ray changes and it indicates the degree of lung parenchyma involvement.…”
Section: Discussionsupporting
confidence: 80%
“…In agreement with other authors (Bourguet et al 1986;Alberts and Van der Schoot 1988;Baughman and Eisentrout 1986), our experience suggests that the absolute quantitation of 67Ga lung uptake appears to be a suitable marker of disease activity in sarcoidosis. It is useful for the delineation of residual X-ray changes and it indicates the degree of lung parenchyma involvement.…”
Section: Discussionsupporting
confidence: 80%
“…However, it may prove a useful measure in future studies. It should be noted that increased gallium activity is quickly suppressed by glucocorticoid therapy, and therefore serial studies have not been useful to monitor response to therapy [59].…”
Section: Chest Imagingmentioning
confidence: 99%
“…8 In patients with pulmonary sarcoidosis, gallium scintigraphy has been shown to be sensitive in detecting lymphadenopathy and parenchymal disease, and useful in assessing disease activity and response to treatment. [11][12][13][14][15][16] Lacrimal gland uptake has also been found to be increased both in patients with pulmonary sarcoidosis and in those with isolated extrathoracic disesase. 10,[17][18][19][20][21][22] Weinreb et al found increased gallium uptake in the lacrimal gland in 87% of sarcoidosis patients versus 31% of patients without sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%